Liczba mieszkańców Zielone j Góry w latach 1945-2010 = Population of Zielona Góra in 1945-2010 - Kurowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The population of Zielona Gora in the years 1945-2003 continually increased. This was the result of 1) expansion of the area of the city from 32 ha to 52.32 ha, 2) the natural growth, especially at the turn of the 1950s/1960s and 1970s/1980s. as well as 3) a positive balance of migration, especially important in the first post-war period and in the 1970s. The population of the city grew from 15.7 thousand in 1946 to 118.7 thousand in 2003.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia